A study of a relativistic quark-diquark model for the nucleon - Gutierrez, C. [UNESP]; De Sanctis, M. (Springer, 2014)
We develop a specific quark-diquark constituent model for the study of the nucleon and its excited states. A relativistic kinetic energy operator is used for both the quark and the diquark. Interaction terms depending on the spin and angular momentum operators are introduced to describe in detail the mass spectrum. Different values of the parameters in the interaction operators are taken for the scalar and axial-vector diquark states. The tensor interaction is also considered in the present model. The baryon spectrum is calculated up to resonance masses of 2 GeV.